Sosialisasi dan Pelatihan Komunikasi Bisnis Penggunaan Aplikasi Point of Sales (POS) Revelle bagi Pelaku UMKM Laundry Sepatu di Wilayah Bekasi - Jawa Barat - Barizki, Rezzi Nanda; Putri, Erita Riski (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Small businesses, including shoe laundry services in Bekasi, West Java, are experiencing significant changes due to the increasing use of digital technology. Many owners are now looking for ways to simplify daily operations and improve their interactions with customers. This community program was developed to help shoe laundry entrepreneurs adopt the Revelle Point of Sales (POS) application, which offers features for recording transactions, managing payments, and communicating more effectively with clients. The program began with a straightforward introduction to the digital cashier system, followed by practical training sessions where participants could directly use the application and practice handling customer transactions. During the workshops, business owners learned not only how to operate the app, but also how to communicate clearly and professionally with customers, especially when dealing with digital payments and record keeping. The results were encouraging: participants reported feeling more confident in managing their finances and interacting with clients, and many found that the Revelle application made their work faster and more organized. To ensure that these improvements continue, ongoing support and consultation were offered, allowing business owners to ask questions and receive guidance as they integrate digital tools into their daily routines. This approach has helped shoe laundry businesses in Bekasi become more adaptable and responsive to the demands of a modern, digital marketplace.